MAPEAMENTO DAS PERCEPÇÕES DE DESEMPENHO DA GESTÃO DA MANUTENÇÃO DE SISTEMAS DE CLIMATIZAÇÃO PREDIAIS O CASO DO INMETRO - Ferraz Júnior, João Evany (2009)
Currently, in order to increase the quality of products and services offered to the market, has been observed a growing concern of the organizations related to the needs achievement of their internal customers. The present work, treats the mapping of perceptions about the performance of building climatization systems maintenance management, from the multifocal perspective: equipment - process - customer. Were studied aspects related to the mapping of the equipment installed plant, to the maintenance processes and to the satisfaction survey with internal customers, which was adapted from the SERVQUAL instrument. Within the organization where this study was developed, that work aims to offer alternatives to the current mainteinance management model, seeking to increase its effectiveness and consequently the internal customers needs achievement. In general, this study treats about the impact of intra-organizational services provided to internal customers - in this case, airconditioning maintenance - on quality of products or services offered by the organization. The results, there was marked the relevance, to the improvement of maintenance management, of the following aspects: mapping and maintenance of updated database of the installed plant; mapping and maintenance of updated management system of quality documents that reflect the processes involved; vulnerabilities identification of the relationship service provider - internal customer through satisfaction survey, highlighting the impact of maintenance activities on the organization core activities.